Differences in lower extremity coordination patterns as a function of sports specialization - Bonnette, S.; Riley, M. A.; Riehm, C.; DiCesare, C. A.; Christy, M.; Wilson, J.; Schille, A.; Diekfuss, J. A.; Kiefer, A. W.; Jayanthi, N.; Myer, G. D. (Journal of Motor Behavior, 2023)
The practice of early sport specialization, defined as intense year-round training in a single sport at the exclusion of others, is increasing in youth athletics. Despite potential benefits, sport specialization may be detrimental to the health of young athletes, as specialization may increase the risk of musculoskeletal injuries—particularly overuse injuries. However, there remains limited knowledge about how sports specialization uniquely alters underlying sports-related motor behavior. The purpose of this study was to compare the variability of movement patterns exhibited by highly sports specialized youth athletes to that of nonspecialized athletes during performance of a sport-specific, virtual reality based cutting task. It was hypothesized that highly specialized athletes would display different patterns of movement coordination compared to nonspecialized athletes during both the run-up phase and cut-and-decelerate phase. In support of the hypothesis, specialized athletes exhibited both intra- and inter-limb coordination that were significantly different than unspecialized athletes. Overall, the results indicate that the highly specialized athletes tended to exhibit greater degrees of coordination but also the ability to break the coordinated patterns of joint angle changes to execute a cutting maneuver, which requires asymmetric demands on the lower extremities while planting on one leg and changing direction.